Dropping out of a peripartum depression mHealth study: participants’ motives and suggestions for improvement - Hanna Wierenga; Konstantina V. Pagoni; Alkistis Skalkidou; Fotios C. Papadopoulos; Femke Geusens (BMC Medical Research Methodology)
Abstract Background Peripartum depression is a common but potentially debilitating pregnancy complication. Mobile applications can be used to collect data throughout the pregnancy and postpartum period to improve understanding of early risk indicators. Aim This study aimed to improve understanding of why women drop out of a peripartum depression mHealth study, and how we can improve the app design. Method Participants who dropped out of the Mom2B study (n = 134) answered closed and open questions on their motives for dropping out of the study, suggestions for improvement, and preferred timeframe of the study. A mix of quantitative and qualitative strategies was used to analyze the responses. Results The most common reasons for discontinuation were lack of time, problems with or loss of the pregnancy, the use of other pregnancy applications, surveys being too lengthy, the app draining too much battery, and participants incorrectly believing that their answers were irrelevant for the study. Participants suggested fewer survey moments, more reminders, and a need for more unique content compared to commercially available apps. Conclusions Researcher who want to use mHealth designs in peripartum studies need to ensure that their study designs are as time-efficient as possible, remind participants about the study, manage expectations about the study and what is expected of participants throughout the study, design their apps to be attractive in a competitive market, and follow-up with participants who are excluded from the study due to pregnancy complications.